Metaphor and the representations of health and illness among the Semai indigenous community in Malaysia - Lendik, L.S. (Universiti Kebangsaan Malaysia Press, 2017)
Diverse methods and approaches have been utilised in researching the cultural bases of health, illness and wellbeing. Understanding the cultural representation of health and illness of particular communities becomes urgent especially when the community concerned is underserved in healthcare. In this project, we sought to examine the representations of health and illness by members of the Semai indigenous community through the use of metaphor analysis, a qualitative method in applied linguistics that attend to how people use language in real-world discourses to understand their conceptualisations of abstract ideas and emotions. From semi-structured interviews with the indigenous Semai people in a village in Malaysia, metaphors of health and illness were identified from the oral stories told by participants. Metaphors were identified and analysed following Lakoff and Johnson’s (1980) conceptual metaphor theory that explains how people understand one idea in a conceptual domain through accessing resources in another conceptual domain. The results show that universal metaphors are dominant in representing embodied experiences while culturally influenced metaphors are important as vehicles of expression derived from their environment and folk beliefs. We argue that while culturally influenced metaphors may mark the participants as strange in their ways of thinking, a closer look at their underlying frameworks finds that they connect with universal bases that are intrinsic to all human experience. Understanding conceptual metaphors can contribute to the expansion of the locus of shared understanding between healthcare providers and the communities they serve. © 2017, Universiti Kebangsaan Malaysia Press. All rights reserved.